Anti-Rhinovirus-specific Activity of the Alpha-sympathomimetic Oxymetazoline - Koelsch, Stephan; Tschaikin, Marion; Sacher, Fritz (Arzneimittelforschung, 2007)
Oxymetazoline (CAS 2315-02-8, OMZ, Nasivin©) known as the active ingredient in nose drops and sprays demonstrates excellent efficacy in the treatment of rhinitis symptoms that are mainly caused by Rhinovirus infections. To elucidate possible modes of action, the antiviral activity of OMZ was studied in vitro on human pathogenic viruses. No in vitro effects were detected against enveloped RNA viruses, Parainfluenza Virus and Respiratory Syncytial Virus and against Adenovirus, a non-enveloped DNA-virus. In contrast, OMZ showed a specific inhibition of Human Rhinovirus (HRV). Analysis of production of HRV-14 and HRV-39 after treatment of infected HeLa cells using plaque-reduction assay and virus titration showed a strong dose-dependent antiviral activity of OMZ. Additional data demonstrated that OMZ did also directly affect HRV-14 infectivity in a dose-dependent manner. Analysis of a cell-protective effect of OMZ showed that pre-treatment of HeLa cells decreased virus adsorption as well as virus replication. Furthermore, OMZ induced a down-regulation of ICAM-1 expression on Tumor Necrosis Factor-α (TNF-α)-stimulated HeLa cells and human umbilical vein endothelial cells. Taken together, these results show that OMZ besides its vasoconstrictive action also possesses potent antiviral and anti-inflammatory activities. Therefore, OMZ does not only reduce rhinitis symptoms but additionally offers a causal therapeutic approach.
Keywords: Alpha-sympathomimetics; CAS 2315-02-8; Intercellular adhesion molecule-1 (ICAM-1); Nasivin© sanft; Oxymetazoline, antiviral activity; Rhinoviruses